2004
DOI: 10.1128/aem.70.2.1097-1103.2004
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic Plants Stimulate the Growth of and Biofilm Formation by Mycobacterium ulcerans in Axenic Culture and Harbor These Bacteria in the Environment

Abstract: Mycobacterium ulcerans is the causative agent of Buruli ulcer, one of the most common mycobacterial diseases of humans. Recent studies have implicated aquatic insects in the transmission of this pathogen, but the contributions of other elements of the environment remain largely unknown. We report here that crude extracts from two green algae added to the BACTEC 7H12B culture medium halved the doubling time of M. ulcerans and promoted biofilm formation. Using the 7H12B medium, modified by the addition of the al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
135
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(143 citation statements)
references
References 27 publications
5
135
2
1
Order By: Relevance
“…In an aquatic environment, M. ulcerans might obtain its energy and carbon from degradation of plant saccharides, as these stimulate growth in vitro (Marsollier et al 2004b). Little is known, however, about its metabolism in insect tissues, although it may be significant that both M. marinum and M. ulcerans encode four potential chitinases/transglycosidases (BuruList/ mast/P4.27.html), one of which is attached to a PE domain and thus is expected to be in the cell envelope.…”
Section: Protein Familiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In an aquatic environment, M. ulcerans might obtain its energy and carbon from degradation of plant saccharides, as these stimulate growth in vitro (Marsollier et al 2004b). Little is known, however, about its metabolism in insect tissues, although it may be significant that both M. marinum and M. ulcerans encode four potential chitinases/transglycosidases (BuruList/ mast/P4.27.html), one of which is attached to a PE domain and thus is expected to be in the cell envelope.…”
Section: Protein Familiesmentioning
confidence: 99%
“…M. ulcerans is associated with aquatic vegetation such as algae (Marsollier et al 2004b); snails and other organisms that feed on algae may serve as passive hosts (Marsollier et al 2004a). One report has shown that M. ulcerans can multiply in the salivary glands of carnivorous water bugs, such as Naucoris cimicoides (Marsollier et al 2002).…”
mentioning
confidence: 99%
“…When more discriminatory methods based on detection of variable number tandem repeats were used, many IS2404-positive environmental samples were reported to lack M. ulcerans (18). In light of these recent fi ndings, the relative frequency or abundance of M. ulcerans among aquatic invertebrates or other environmental reservoirs, remains tenuous, and thus, the role of aquatic insect vectors is uncertain.A series of laboratory experiments provided initial evidence for biting hemipteran vectors of M. ulcerans (19)(20)(21)(22)(23). Marsollier et al (9,24) demonstrated that a South American isolate of M. ulcerans could survive and multiply within the salivary glands of aquatic bugs indigenous to France (Naucoridae: Naucoris cimicoides).…”
mentioning
confidence: 99%
“…Une étude histologique a montré une localisation prépondérante sinon exclusive du bacille dans les glandes salivaires des punaises, et ce, paradoxalement, sans aucun dommage du parenchyme tissulaire malgré la capacité du bacille à produire une toxine cytotoxique [8,9]. Par ailleurs, nous avons rapporté que des plantes aquatiques servaient de support à la formation de biofilms [10,11] et pouvaient être à l'origine de la contamination transitoire de proies phytophages (mollusques) des punaises. Un travail de terrain réalisé dans des zones endémi-ques au Bénin a permis de confirmer la validité des données sur l'écologie et la transmission de M. ulcerans des végétaux aquatiques à l'homme via des punaises d'eau [8].…”
Section: éCologie Et Transmission De M Ulceransunclassified